2021
DOI: 10.1177/00034894211045771
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Opioid Use in Post-Surgical Management of Patients With Head and Neck Cancer

Abstract: Objective: This study aims to identify clinical and socioeconomic factors associated with long-term, post-surgical opioid use in the head and neck cancer population. Methods: A single center retrospective study was conducted including patients diagnosed with head and neck cancer between January 1, 2014 and July 1, 2019 who underwent primary surgical management. The primary outcome measure was continued opioid use 6 months after treatment completion. Both demographic and cancer-related variables were recorded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[14][15][16][17][18] Studies have documented the dangers of overprescribing and long-term opioid abuse. [19][20][21][22] More than 70% of postoperative opioid prescriptions are unused and are subsequently stored in unlocked locations in as many as 77% of cases. 23,24 These excess opioids are at high risk for diversion to nonmedical opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] Studies have documented the dangers of overprescribing and long-term opioid abuse. [19][20][21][22] More than 70% of postoperative opioid prescriptions are unused and are subsequently stored in unlocked locations in as many as 77% of cases. 23,24 These excess opioids are at high risk for diversion to nonmedical opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a wide range of pain levels and medication requirements associated with head and neck oncologic surgical procedures . Studies have documented the dangers of overprescribing and long-term opioid abuse . More than 70% of postoperative opioid prescriptions are unused and are subsequently stored in unlocked locations in as many as 77% of cases .…”
Section: Discussionmentioning
confidence: 99%